Upper respiratory tract infections and their association with knowledge, attitude and practice among Malaysian hajj pilgrims of 2007 A.D (1428 h)[RS1-441]. - Mansoor, Sarab Malik (2009)

(untitled)
Setiap tahun lebih dari dua juta Muslim daripada lebih 140 negara menunaikan ibadat haji di Mekah dan Madinah.